The Effect of Board Governance and CEO Attributes Towards Corporate Performance of Malaysian Public Listed Financial Companies - Yau, Josephine Tan Hwang; Khor, Mei Szee; Liwan, Audrey (UNIMAS Publisher, 2020)
This paper investigates the relationship between corporate governance, CEO attributes and firm performance of public listed financial companies in Malaysia from 2008 to 2017. There are several theories employed in the studies whereby the agency theory and resource dependency theory suggest that the board size have a positive impact on firm performance. In contrast, stewardship theory suggests smaller board size positively impacts the firm performance and prospect theory suggested that every person perceives and values gains and losses differently, and this affects the decision making. The firm performance has been measured using the return on equity (ROE) and return on assets (ROA). The data of the variables of board size, board independence, board meeting, CEO duality, CEO age and CEO gender are manually obtained from the annual reports, while the financial data include firm performance, capital expenditure and leverage are obtained from the Thomson Reuters Datastream. The research method employed in this study is the panel regression analysis. The findings of this study suggest that there is a positive and significant relationship between board size and firm performance and a positive and significant relationship between board independence and firm performance. Meanwhile, board meeting is found to have mix relationship with the firm performance. Furthermore, our result also shows CEO age and male CEO exhibit positive impact on firm performance.